The Role of Classification of Endoscopic Sinus Surgery in Surgical Planning (Global Journal of Medical Research, 2023)
Endoscopic sinus surgery being an approach there is no proper classification system to address the extent of surgery required for Sinonasal pathologies The current study attempts to propose and evaluate the role and efficacy of a classification system for endoscopic sinus surgery in addressing various Sinonasal and skull base pathologies Materials and methods It s a prospective study that included 50 patients We classified ESS into six types based on the extent of surgery After thorough evaluation depending on the extent of the disease all 50 patients were planned and treated according to the classification Patients were followed for one year
Keywords: endoscopic sinus surgery; sino nasal pathologies; CRS; ESS